Optimised oligonucleotide substrates to assay XPF-ERCC1 nuclease activity for the discovery of DNA repair inhibitors - Thomas, A; Brolih, S; McGouran, J; El-Sagheer, A; Ptchelkine, D; Jones, M; McDonald, N; McHugh, P; Brown, T (Royal Society of Chemistry, 2019)
We report the design and optimisation of novel oligonucleotide substrates for a sensitive fluorescence assay for high-throughput screening and functional studies of the DNA repair enzyme, XPF-ERCC1, with a view to accelerating inhibitor and drug discovery.